The business actor and business management. Issue 2 (12th June 2017) - Munksgaard, Kristin B.; Ford, David
Abstract : Purpose: IMP literature has developed the conceptualisation of a business landscape comprised of varying combinations of more or less interdependent activities, resources and actors, the form of which are defined by the interactive processes in which they are involved. However, the conceptualisation of the interactively defined business actor presents challenges to the understanding of the nature of business and the process of management. The purpose of this paper is to discuss what it is to be a manager in the complex interactive business landscape and the capabilities needed by business managers. Design/methodology/approach: Few, if any, IMP studies have systematically addressed the concept of the business actor directly and the authors do not have a well-developed framework for analysing actors from the perspectives of interaction and networks. This paper analyses the evolving semantics of the concepts of the interactive business actor within some of the literature associated with the IMP research tradition, using the software Leximancer. Findings: The paper integrates the analysis into a preliminary framework for describing the characteristics of the interactive business actor. The paper concludes by using this framework to suggest some of the capabilities that are required by the interactive business actor. Originality/value: The analysis points to the ways that ideas of the business actor and business acting have developed in the literature. The analysis highlights some of the ways in which the development of these concepts is incomplete and points to potentially fruitful ways in which conceptual and empirical research could proceed.